Power plant ash and slag waste management technological direction when Kansk-Achinsk brown coal is burned; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Lihach S. A. Snejana; Kulesh R. N. Roman Nikolaevich; Nikolaeva V. I. Valentina Ivanovna; Orlova K. Yu. Kseniya Yurievna; Ilyasova A. S. Aygul (2017, 2017)
Title screen